IMPLEMENTATION OF THE (MFEP) MULTIFACTOR EVALUATION PROCESS METHOD IN DETERMINING SCHOOL RENOVATION - Siti Nurkumala Dewi; Hambali Hambali; Sri Rezki Maulina Azmi (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: The Government of Indonesia has established National Education Standards relating to facilties and infrastructure with the aim that every school-age child can enjoy a proper and quality education. However, in Batu Bara District, educational problems cannot be handled optimally, especially in the suurbs, there are still many school buildings in unfit for use conditions which are quite apprehensive and no longer sufficient to accommodate the increasing number of students each year. Realizing the importance of education, the Government of Batu Bara Regency has provided a budget for school renovations which are considered to be inadequate. For policy making that is oriented towards equal rights to obtain quality and relevant education, to create a computer- based system and use the Multifactor Evaluation Process method which is implemented into the Sublime Text 3 programming language, and theb MySQL database, to assist policy makers in analyzing data school- school data that is noy suitable for renovation. This system is expected to be able to provide suggestions and provide the information needed to prioritized for enovation. Keywords: decision support system; multifactor evaluation process; school renovation  Abstrak: Pemerintah Indonesia telah menetapkan Standar Nasional Pendidikan yang berkaitan dengan sarana dan prasarana dengan tujuan agar setiap anak usia sekolah dapat menikmati pendidikan yang layak dan bermutu. Namun di Kabupaten Batu Bara masalah pendidikan masih belum dapat ditangani secara optimal, terutama di daerah pinggiran masih banyak bangunan sekolah dengan kondisi yang tidak layak pakai dan cukup memprihatinkan dan tidak lagi memadai untuk menampung siswa yang bertambah setiap tahunnya. Sadar akan pentingnya pendidikan, Pemerintahan Kabupaten Batu Bara telah menyediakan anggaran untuk  renovasi  sekolah yang dinilai kurang layak. Untuk pengambilan kebijakan yang berorientasi pada kesamaan hak untuk memperoleh pendidikan yang bermutu dan relevan maka dibuat sistem berbasis computer dan menggunakan metode Multifactor Evaluation Process yang diimplementasikan kedalam bahasa pemrograman Sublime Text 3, dan database MySQL, untuk membantu para pemangku kebijakan dalam menganalisis data-data sekolah yang tidak layak untuk dilakukan renovasi. Sistem ini diharapkan dapat memberikan usulan dan menyediakan informasi yang dibutuhkan untuk   memprioritaskan sekolah mana yang lebih didahulukan untuk dilakukan renovasi. Kata Kunci : multifaktor evaluation process; renovasi sekolah; sistem pendukung keputusan